Effect of fish oil supplementation on fasting vascular endothelial function in humans: a meta-analysis of randomized controlled trials. - Wei Xin (Public Library of Science (PLoS), 2012)
Background Effect of fish oil supplementation on flow-mediated dilation, an index of endothelial function in humans, remains controversial. We performed a meta-analysis to determine whether fish oil supplementation could improve endothelial function. Methods Human intervention studies were identified by systematic searches of Medline, Embase, Cochrane's library and references of related reviews and studies. A random-effect model was applied to estimate the pooled results. Meta-regression and subgroup analyses were performed to evaluate the impact of study characteristics on the effect of fish oil supplementation on flow-mediated dilation. Results A total of sixteen records with 1,385 subjects were reviewed. The results of the pooled analysis showed that fish oil supplementation significantly improved flow-mediated dilation (weighed mean difference: 1.49%, 95% confidence interval 0.48% to 2.50%, p = 0.004). Meta-regression and subgroup analysis suggested that the quality of included studies were inversely related to the overall effect (regression coefficient  = -1.60, p = 0.04), and the significance of the effect was mainly driven by the studies with relatively poor quality. Sensitivity analysis including only double-blind, placebo-controlled studies indicated fish oil supplementation has no significant effect on endothelial function (weighed mean difference: 0.54%, 95% confidence interval -0.25% to 1.33%, p = 0.18). Besides, normoglycemic subjects or participants with lower diastolic blood pressure seemed to be associated with remarkable improvement of endothelial function after fish oil supplementation. Conclusions Although current evidence suggested a possible role of fish oil in improving endothelial function, large-scale and high-quality clinical trials are needed to evaluate these effects before we can come to a definite conclusion.